Organising pneumonia in common variable immunodeficiency. (7th June 2013) - Boujaoude, Ziad; Arya, Rohan; Rafferty, William; Dammert, Pedro
Abstract : Common variable immunodeficiency (CVID) is the most common of the primary immunodeficiency disorders. Pulmonary manifestations are characterised by recurrent rhinosinusitis, respiratory tract infections and bronchiectasis. Less commonly the lung may be affected by lymphoid disorders and sarcoid-like granulomas. Organising pneumonia (OP) is a rare pulmonary manifestation. We report the case of a 32-year-old woman with CVID who presented with fever, dyspnoea and persistent lung infiltrates despite antibiotic therapy. CT of the chest showed bilateral patchy alveolar infiltrates. Pulmonary function tests revealed moderate restriction and reduction in diffusion capacity. Initial bronchoscopy with transbronchial biopsies did not yield a diagnosis but surgical lung biopsies identified OP. Significant clinical, radiographic and physiological improvement was achieved after institution of corticosteroid therapy.